The position of the longest intron is related to biological functions in some human genes - Dvorak, Pavel; Hanicinec, Vojtech; Soucek, Pavel (Frontiers in Genetics, 2023)
The evidence that introns can influence different levels of transfer of genetic information between DNA and the final product is increasing. Longer first introns were found to be a general property of eukaryotic gene structure and shown to contain a higher fraction of conserved sequence and different functional elements. Our work brings more precise information about the position of the longest introns in human protein-coding genes and possible connection with biological function and gene expression. According to our results, the position of the longest intron can be localized to the first third of introns in 64%, the second third in 19%, and the third third in 17%, with notable peaks at the middle and last introns of approximately 5% and 6%, respectively. The median lengths of the longest introns decrease with increasing distance from the start of the gene from approximately 15000 to 5000 bp. We have shown that the position of the longest intron is in some cases linked to the biological function of the given gene. For example, DNA repair genes have the longest intron more often in the second or third third. In the distribution of gene expression according to the position of the longest intron, tissue-specific profiles can be traced with the highest expression usually at the absolute positions of intron 1 and 2. In this work, we present arguments supporting the hypothesis that the position of the longest intron in a gene is another biological factor modulating the transmission of genetic information.